(3YbjdI CJQGH GdbUGFO aj CSfi GdebGUOs - (3GdbGSe Hf ajQg Hf Nda Hf CMeO GdQYjfj, CHh eMeO GdTGWHj,J (B590 (3g` s ((3CHhHcQ eMeO Ydi Hf eMeO EHQGgje GdMSjfj s)
(3ChdgG (B:s
(3hHYO aGdeSJYGf Gddg aj SHH, jgOj Edi Sff GdeQShe s
(3BNQgG (B:s
(3hGdTjY GdegGLQjf hef Chj hef fUQGg JVGMc GdRgQ eSQhQC JeJ HMeO Gddg hYhfg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3haj BNQgG ahGFOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B110s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1159s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs